2012
DOI: 10.1143/apex.5.091002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Pressure Inert Gas Annealing on AlON/Ge Gate Stacks

Abstract: We investigated germanium (Ge) metal–insulator–semiconductor (MIS) gate stacks with aluminum oxynitride (AlON) thin dielectric film. We found that high-pressure inert gas post deposition annealing (PDA) using N2 or Ar gas dramatically improved the electrical properties of AlON/Ge MIS gate stacks. The advantage of this process over high-pressure O2 oxidation or annealing, which produce excellent Ge gate stacks, is that no further interface layer growth in the N2 or Ar PDA is expected. We expect that thin AlON f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…3.3. 77,78) So GeO desorption could be reduced and the interface properties might be improved by fine-tuning the N profile in GeO 2 . As we did not have an appropriate technique for the optimum nitridation of Ge for N not to be located at the interface, we stopped studying the GeON gate stack.…”
Section: Materials Approachmentioning
confidence: 99%
“…3.3. 77,78) So GeO desorption could be reduced and the interface properties might be improved by fine-tuning the N profile in GeO 2 . As we did not have an appropriate technique for the optimum nitridation of Ge for N not to be located at the interface, we stopped studying the GeON gate stack.…”
Section: Materials Approachmentioning
confidence: 99%
“…Notably, C Lee et al has revealed a novel high-pressure oxidation (HPO) of Ge would dramatically improve Ge/GeO 2 interface [7]. Besides of that, post deposition annealing (PDA) by varying different annealing parameters such as annealing ambient, temperature and duration is widely used for various Ge/dielectric interface reparement such as HfTiON/Ge [11], Al 2 O 3 /Ge [12,13], HfO 2 /Ge [14], Y 2 O 3 /Ge [15], and AlON/ Ge [16]. For example, X Zou et al have reported that wet-N 2 annealing can greatly suppress the growth of unstable low-k GeO x at the high-k HfTiON/Ge interface, thus resulting in less interface states and di electric charges [11].…”
Section: Introductionmentioning
confidence: 99%